Challenges of Civic Participation at EU – Level During COVID-19 Pandemic: European Citizens’ Initiative - DRUGĂU-CONSTANTIN Andreea Ligia; ANGHEL-SIENERTH Andra Karla (Applied Research in Administrative Sciences)
One key factor in achieving the modernization both of a country and of a supra-national organization is to have functional mechanisms that facilitate the participation of citizens. This paper aims to explore the efficacy of the European Citizens’ Initiative and its development during the COVID-19 pandemic. The study begins with the theoretical framework covering both several theories on the topic of civic engagement and the legislation ensuring the functioning of the European Citizens’ Initiative. It continues with an analysis of the initiatives that were submitted to conclude if the mechanism is successful. The case study focuses on the effects of the COVID-19 pandemic on both the functioning of this mechanism and on the characteristics of the proposed initiatives. The article does not study the impact of the approved initiatives or the relevance of their subject; it only analyses the success rate of this mechanism in terms of approval and the effects of the pandemic on the procedure and on the specificity of the initiatives.